Social listening applied to tailor communication on immunization in the Republic of Moldova - Timotin, Alina; Paladi, Adriana; Mita, Valentin; Chihai, Valeria; Lozan, Oleg (European journal of public health, 2025)
Although the Republic of Moldova had good vaccination rates, anti-vax messages have recently begun to spread, eroding the population’s confidence. Vaccination coverage against measles, mumps, and rubella at the target age of 12 months decreased from 95% in 2008 to 83% in 2021. The recent measles outbreak in Romania and three confirmed cases in Moldova, combined with the refugee crisis, have highlighted the importance of vaccination and sparked online conversations on this subject. A mixed-methods study was conducted, involving social listening activities on immunization using the Talkwalker software and qualitative analysis of the identified narratives. Out of 450 identified comments, 30 were selected for further analysis. Over 5 months, a total of 865 results were obtained, with an engagement rate of 6300. The peak in results occurred between 11 and 18 December, driven by the recent measles outbreak in Romania, which saw several confirmed cases and one death, as well as the first cases of measles in Moldova after 3 years. However, no significant increase in the engagement rate was recorded. Comments on immunization tended to reflect distrust in authorities and doctors, political and ideological views, and a lack of knowledge about the risks of vaccine-preventable diseases. The analysed conversations are assessed as having a low risk of spreading, though some employ techniques to influence or manipulate behaviours. The topic of vaccination is used to promote political ideologies through messages issued by the mass media. The information vacuum must be filled with messages designed to produce attitude change regarding vaccination.